Effectiveness of the Complete Systematic Land Registration Program (PTSL) In Rembang Regency - Dinata, Rendi Apri; Riyanto, Taufan Fajar (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to analyze: 1) The implementation of complete systematic land registration (PTSL) at the BPN/ATR of Rembang Regency. 2) Obstacles and solutions to the implementation of complete systematic land registration (PTSL) at the BPN/ATR of Rembang Regency. This type of research is sociological juridical research. The approach method in this study is a descriptive analytical approach. The types of data in this study are primary data and secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses field studies and literature studies. The analysis in this study is qualitative. The results of the study concluded: 1) The implementation of complete systematic land registration (PTSL) at the BPN/ATR of Rembang Regency, especially Sarang District, was carried out in accordance with Presidential Instruction Number 2 of 2018 and Regulation of the Minister of ATR/BPN Number 6 of 2018, with effective coordination between the BPN, local government, village officials, and the community. The 100% target by 2024 was achieved, providing positive impacts in the form of legal certainty, protection of ownership rights, orderly land administration, increased access to financing, and public legal awareness. This PTSL is in line with the theory of legal certainty, legal protection, the legal system, law enforcement, and the principles of Islamic justice that affirm equal rights to land. 2) Obstacles to PTSL in Rembang Regency include: (a) administrative-technical, such as mistaken identity, differences in measurement results, and overlapping land plots; (b) socio-economic, such as the burden of non-BPN costs, low understanding of the benefits of certificates, and misperceptions regarding taxes; and (c) regulatory-implementation, such as suboptimal electronic certificates and lack of initial mapping of land plots. Solutions taken include strict document verification, additional measuring personnel, strengthening the role of village officials, re-measurement, community-based outreach, subsidies for non-BPN costs, NJOP-based tax education, and expanding the implementation of integrated e-certificates based on spatial and legal data. Keywords: Effectiveness; Land Registration; PTSL.